Učenje jezika je investicija - Zver, Sofija (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2012)
The importance of the knowledge of the Slovenian, Hungarian and a foreign language in relation to employment in the ethnically mixed area of Prekmurje is defined in the introduction of the article. Different research approaches in dealing with the link between knowledge of language and workplace are presented in the analytically relevant literature. Selected empirical research data with regard to informal language learning at the language schoolsin the ethnically mixed area of Prekmurje is presented.
Keywords: Prekmurje; učenje jezika; jezikovne šole; zaposlovanje; narodno mešana območja; raba jezika; večjezičnost